EFFECTIVENESS AND SAFETY OF INFLIXIMAB IN PATIENTS WITH EARLY AND LATE JUVENILE RHEUMATOID ARTHRITIS - Е.I. Alexeeva; T.V. Sleptsova; S.I. Valieva; T.M. Bzarova; R.V. Denisova; A.O. Lisitsyn ("Paediatrician" Publishers LLC, 2010)
The article presents results of a study of effectiveness and safety of infliximab - monoclonal antibodies to the tumor necrotizing factor (TNF) in treatment of 100 patients11 months - 17 years old with early and late articular types of juvenile rheumatoid arthritis. The duration of treatment was 3 months - 2 years. Infliximap was delivered intravenously by scheme: infusion on 0, 2nd, 6th weeks and then every 8th week. The single dose of infliximab in patients with early rheumatoid arthritis was 6.7 (5.5; 9.0) mg/kg, with late type - 6.0 (5.0; 7.0) mg/kg of body weight. 102 weeks of treatment with anti-TNF-agent provided development of clinical remission, decrease and normalization of laboratory tests of disease's activity, total restoration of joint's function, increase of quality of life (on 97% in patients with early type, and 72% 0 in ones with late type). The drug was abolished in 39 (39%) of patients, 23% - due to the development of secondary inefficiency, and 11% - due to the development of unfavorable effects.Key words: children, early and late rheumatoid arthritis, treatment, infliximab.(Voprosy sovremennoi pediatrii - Current Pediatrics. - 2010;9(3):30-42)